The Interactive European Grid: Project Objectives and Achievements - Marco, J.; Campos, I.; al., et (Computing and Informatics, 2012)
The Interactive European Grid (i2g) project has set up an advanced e-Infrastructure in the European Research Area specifically oriented to support the friendly execution of demanding interactive applications. While interoperable with existing large e-Infrastructures like EGEE, i2g software supports execution of parallel applications in interactive mode including powerful visualization and application steering. This article describes the strategy followed, the key technical achievements, examples of applications that benefit from this infrastructure and the sustainable model proposed for the future.